COMPARATIVE CELLULAR IMMUNE HOST RESPONSE IN ACUTE VS HEALED LESIONS OF CUTANEOUS LEISHMANIASIS - Rahman, Simeen Ber; Bari, Arfan ul (Journal of Ayub Medical College Abbottabad, 2006)
Background: Cutaneous leishmaniasis (CL) has become a major public health problem in Pakistan and research is now focused to characterize the host’s immune response, its clinical correlation and subsequent implications in management in this disease. This study was done to evaluate cellular immune host response in patients with active and healed CL and its possible implications in prevention of disease in susceptibles. Methods: This cross sectional and comparative study was conducted in Armed Forces Institute of Pathology (AFIP) and Military Hospital (MH) Rawalpindi (1998-2000). 30 biopsies of active skin lesions and 15 biopsies from healed lesions, after processing, were studied for various immunophenotype cells by using monoclonal antibodies. Total and differential T cell counts were recorded in these skin tissues. Non parametric Kruskal-Wallis Test for one way ANOVA was used to compare the median cell counts between active, healed and normal skin and p-value <0.05 was considered significant. Results: The total cell counts, CD3+ cells and CD57+ (NK) cells were found statistically different (p=<0.001) when active forms of the disease were compared with healed lesions and normal skin tissue. The difference was not significant (p=>0.05) on comparing healed lesions with normal skin tissue biopsies except in case of CD3+ cell counts (p=<0.05). However, CD4+, CD8+ and CD19+(Plasma cells) counts were never seen significant (p=>0.05) on comparison. Conclusion: NK cells and gamma delta cells seem to be responsible for limitation of the disease and elimination of the parasite from the lesion in cases of acute cutaneous leishmaniasis. Keywords: Leishmaniasis, Cutaneous leishmaniasis, Cellular immune host response